Investigation on electric motor braking control system for electric powered wheelchair - Muhammad Asyraf, Shahrom (2020)
In recent years, research on Electric Powered Wheelchair (EPW) has been widely studied due to its high importance of mobility for disabled people. During descent on a slope, the manual braking system is commonly used to control the speed by gripping the brake lever. However, the task becomes difficult if the user is an elderly or paralyzed due to their body’s deficiencies. As a result, the possibilities of collision and injuries to occur are high. In this study, the automatic electric motor braking control that is known as Hill Descent Control (HDC) is proposed to increase the safety of EPW during descending on slopes. Since the electric motor has an advantage which can generate the torque during braking, the plugging braking is integrated with the HDC system to control the speed of the EPW according to the desired speed from the user. The analysis of this study is divided into three phases; investigation of braking performance using electrical braking, development of active braking control system in the embedded system as well as the simulation environment and analysis on active braking control system in experimental and simulation work. From the experimental results, the plugging brake is most suitable to integrate with the active brake control system compared to the regenerative and dynamic brake. In the plugging brake, by changing the plugging voltage from 0.5 V to 4.5 V, a variety of dynamic behaviour effects such as braking distance, tire speed and slip ratio can be achieved. Meanwhile, from the analysis of active braking control system that was integrated with plugging braking, both of the experimental and simulation analysis results show the speed of EPW can be maintained at the desired speed of